Permainan Ular Tangga: Media Pembelajaran Siswa Kelas V Sekolah Dasar - Gusti Ayu Komang Setiani; Dewa Ayu Puteri Handayani (Universitas Pendidikan Ganesha, 2022)
The lack of availability of learning media that adapts a traditional game causes teaching and learning activities to become monotonous, especially in social studies content. This affects the decreasing interest of students to be active in learning. The purpose of this research is to create a social media snake and ladder game for fifth grade elementary school students. This type of research is development research based on the ADDIE development model. The subjects of this study consisted of 2 material experts, 2 media experts, 2 practitioners, and 10 students for the small group test. The data collection method in this study applies a questionnaire method with a rating scale instrument as a data collection instrument. The data analysis technique used is descriptive qualitative and quantitative analysis techniques. The data obtained were then analyzed to calculate the validity, feasibility, and practicality of the media. The results of the validity analysis are in the range of scores of 4.21 ≤ Va < 5.00 with very valid criteria. The average media feasibility assessment score shows a percentage above 90% in the very feasible category, and the media practicality assessment in terms of student responses gets a score of 92.2% which is categorized as very practical. Based on the results of the analysis, the Social Sciences Snakes and Ladders game media for fifth grade elementary school students on the topic of our friend's environment was declared to be very valid, feasible, and practically applied to teaching and learning activities.